Glufosinate Resistance Level is Proportional to Phosphinothricin Acetyltransferase Gene Expression in Glufosinate-Resistant Maize - Krenchinski, Fabio H. [UNESP]; Carbonari, Caio A. [UNESP]; Cesco, Victor J. S. [UNESP]; Albrecht, Alfredo J. P.; Campos Arcuri, Mariana De Lara [UNESP]; De Godoy Maia, Ivan [UNESP]; Velini, Edivaldo D. [UNESP] (American Chemical Society (ACS), 2018)
Phosphinothricin acetyltransferase (pat) gene confers resistance to glufosinate by transforming this herbicide into N-acetyl-l-glufosinate (NAG). The pat gene was inserted in six maize hybrids (Herculex, Agrisure TL, Herculex Yieldgard, Leptra, Viptera 3, Power Core) as a selectable marker, and its expression was evaluated by qPCR in comparison with the maize glufosinate-susceptible cultivar VTPRO. In addition, the levels of NAG, glufosinate degradation, ammonia accumulation, electron transport rate (ETR), visual injury, and biomass were also investigated. The VTPRO, Herculex, Agrisure, and Viptera showed lower pat gene expression, and consequently lower NAG contents and glufosinate degradation, as well as reduced ETR and biomass accumulation. In contrast, greater ammonia accumulation and higher visual injury were observed. The ranking of pat gene expression was Leptra > Power Core > Herculex Yieldgard ≫ Herculex > Agrisure TL = Viptera 3 > VTPRO. This gene expression was proportional to the glufosinate resistance level observed in each maize hybrid.
Keywords: ammonium accumulation; electron transport rate; glufosinate ammonium; l -phosphinothricin; marker gene; N-acetyl- l -glufosinate; pat gene; Zea mays L.